Tactical Games Approach Dalam Pembelajaran Bolavoli Siswa Sekolah Dasar - - Sri Mawarti (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Volleyball learning for primary school has distinctive approach. One oflearning approach was decisively hasten volleyball basically skill with tactical gamesapproach. This approach giving many chances for student to actively learninginvolvement.A game is a main element to this age. Giving some problem on learning process,gambit to engage primary school student to get a problem solving at appear difficultieson the learning process. With tactical games approach, teacher led as a learningmediator and facilitator which student helping to skill maximal to be volleyball skillabilities.Plays are a way to creativity and flexibility developmental. In volleyball learning forprimary school, tactical games approach has function as a cooperative play. Its teamwork availability, duty allocation, and lead for they are involvement on this games toattain some aim.Kata Kunci: Pendidikan Jasmani, Pembelajaran Bola Voli, Tactical Games Approach,Sekolah Dasar.